A novel fabrication strategy for doped hierarchical porous biomass-derived carbon with high microporosity for ultrahigh-capacitance supercapacitors. Issue 34 (15th August 2019) - Chang, Chengshuai; Li, Miao; Wang, He; Wang, Shulan; Liu, Xuan; Liu, Huakun; Li, Li
Abstract : Nitrogen doped biomass derived carbons with high microporosity were prepared through micromolecular template method and showed ultrahigh capacitance as the supercapacitor electrodes. Abstract : Biomass derived carbons with a high surface area, an appropriate pore size distribution, and abundant heteroatoms are viewed as intriguing electrode materials for the assembly of high performance supercapacitors, while achieving both the pore structure and the heteroatom engineering simultaneously still remains a challenge. In the present work, we propose a facile and novel synthesis strategy with urea as a micromolecular dual-functional template to prepare an interconnected nitrogen-doped hierarchical porous carbon material with high microporosity (86.8%) and small mesopore size (2–4 nm) from Firmiana simplex fluff (FSF) as the biomass precursor. After Co 2+ catalyzed graphitization and molten KOH treatment, the as-prepared carbon also showed a high surface area (2351 m 2 g −1 ) and low internal resistance for charge transfer. The as-prepared carbonaceous electrode delivered a record high capacitance value of 836 F g −1 at a current density of 0.2 A g −1 in 2 M H2 SO4 . An assembled symmetric supercapacitor also achieved a record high aqueous energy density for biochar of 36.50 W h kg −1 at a power density of 140 W kg −1 in 2 M Li2 SO4 . This method provides new insight into the pore structure and defect engineering of carbon and also represents an effective approach to the fabrication of high-capacitance/energy density biochar electrodes.